Automation, heat loss reduction and optimum positioning of solar hot water system with storage tank in Bangladesh - Ferdous, Jannatul; Swjo, Rafiur Rahman; Hasan, Raied; Azad, AKM (© 2016 Published by BRAC University, 2017)
This article was published in the BRAC University Journal [© 2016 Published by BRAC University].